Implementation of the Al-Mudharabah Al-Musytarakah Agreement in Islamic Banking Financial Institutions - Kholilur Rahman; Naerul Edwin Kiky Aprianto; Muhammad B. Jasmi (DAS Institute, 2024)
Profit and loss sharing is a system used as an operational activity in Islamic banking. Therefore, the most important theory to be raised in this research is the mudharabah contract. Departing from the character of banking in general which is closely attached to Islamic banking as an intermediary institution, a new breakthrough is needed through the study of contemporary mudharabah contracts called al-mudharabah al-musytarakah as the most relevant theoretical basis. This is because the working mechanism of Islamic banks cannot be separated from funding and financing activities, and the bank's position is in the middle of these funding and financing activities. The mudharabah that we know from time to time only involves two parties, whereas in banking it involves three parties. With this qualitative casuistic research, the aim is to obtain data regarding the implementation of the al-mudharabah al-musytarakah contract in Islamic banking. The implementation of the al-mudharabah al-musytarakah agreement in Islamic banking is realized in various funding products, both savings and deposit products, and is related to mudharabah financing as a financing product.